2018
DOI: 10.1016/j.peh.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the motivations for anabolic-androgenic steroid use: The role of muscle dysmorphia and self-esteem in long-term users

Abstract: Background: The use of Anabolic-androgenic steroids (AAS) among the non-competitive weightlifting community has increased considerably in the UK in recent years, presenting a public health issue. The motives behind use have received considerable attention, with motivations linked to body dissatisfaction, low self-esteem, and more recently, muscle dysmorphia (MD). However, the causal roles of MD and self-esteem in AAS use remain unclear. Therefore, this paper examines the origins and changes to motivations in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 38 publications
3
31
0
7
Order By: Relevance
“…The use of AAS for performance and image enhancement is a growing concern in these countries; however, knowledge, understanding, and awareness of health harms related to AAS appear to be varied and somewhat limited. Most studies in this review reported AAS users as single and in fulltime employment, highlighting high rates of employment, similar to studies in the UK (Baker et al 2008;Begley et al 2017;Greenway and Price 2018), Australia (Jacka et al 2017), and the USA (Pope et al 2014a(Pope et al , 2014b. Educational status of AAS current and former users in the Middle East was highest in the 'higher education' range which corroborates research in Australia (Cohen et al 2007) and the USA (Westerman et al 2016).…”
Section: Discussionsupporting
confidence: 84%
“…The use of AAS for performance and image enhancement is a growing concern in these countries; however, knowledge, understanding, and awareness of health harms related to AAS appear to be varied and somewhat limited. Most studies in this review reported AAS users as single and in fulltime employment, highlighting high rates of employment, similar to studies in the UK (Baker et al 2008;Begley et al 2017;Greenway and Price 2018), Australia (Jacka et al 2017), and the USA (Pope et al 2014a(Pope et al , 2014b. Educational status of AAS current and former users in the Middle East was highest in the 'higher education' range which corroborates research in Australia (Cohen et al 2007) and the USA (Westerman et al 2016).…”
Section: Discussionsupporting
confidence: 84%
“…In the context of a muscularity‐centred culture, some men overtly stated that AAS were used specifically to prepare for night clubbing and/or festival appearances. Certainly, the presence of reinforcers such as increased self‐esteem, body confidence, and social acceptance, have been shown in previous work to be important in maintenance of AAS use (Greenway & Price, ). Unlike recreational drugs, steroids do not necessarily produce an immediate high or intoxicating effect.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike recreational drugs, steroids do not necessarily produce an immediate high or intoxicating effect. The literature available suggests that the reward experienced by the user comes much later in the form of these secondary reinforcers (Greenway & Price, ). In the present investigation, even though the participants did not describe themselves as AAS dependent, they exhibited many other features suggestive of dependence, such as the use of the drugs in larger amounts than originally intended, commitments of considerable time and money to obtain supplies of the drugs, and continued use of various drugs despite adverse physical or psychological effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations